PERLINDUNGAN HUKUM ANGGOTA KOPERASI SIMPAN PINJAM SEJAHTERA BERSAMA ATAS HOMOLOGASI YANG TIDAK OPTIMAL - Niken Raras Kusumastuti; I Made kanthika (CV. Bunda Ratu, 2024)
Koperasi Simpan Pinjam Sejahtera Bersama (KSP-SB) as one of the savings and loan cooperatives established since 2004 and has developed in several provinces in Java with 97 service offices, a total of around 181,000 members and is one of the best and largest savings and loan cooperatives in Indonesia. Since early 2020, KSP-SB there has been a failure to pay profit sharing to members which resulted in KSP-SB being in PKPU. PKPU has ended with a peace agreement through a homologation decision, but KSP-SB did not implement the peace agreement. The problem raised in this study is what form of legal protection is provided to KSP-SB members after the homologation decision. The research method used is normative legal research with a statutory approach and a case approach. Legal materials are sourced from primary, secondary and tertiary legal materials which are analyzed based on the theory of legal protection. The results of the study show that the form of legal protection that can be provided to KSP-SB members is repressive legal protection which aims to restore the losses experienced by KSP-SB members. The conclusion of this study is that the management of KSP-SB must be responsible for making payments to members in accordance with the peace agreement in the homologation decision, so that legal protection and legal certainty are achieved for the members of KSP-SB.